Relationship Between Nurses' Personality and Patient Satisfaction - Adhikari, Anjali; Giri, Mahendra; Hamal, Janga Bahadur (International Journal of Atharva, 2025)
The study explores the impact of nurses’ personality traits on patient satisfaction, a crucial determinant of healthcare quality. Patients are the cornerstone of the healthcare system, and their satisfaction directly influences the reputation and success of healthcare facilities. A satisfied patient is more likely to recommend a healthcare center to others, highlighting the significance of understanding factors that enhance patient satisfaction. This research examines how nurses' personality traits, including empathy, communication style, and emotional stability, affect patients' trust and overall satisfaction with healthcare services. The study investigates whether demographic variables such as age, gender, and education level influence patients' perceptions of nurses’ behavior. A quantitative research design was utilized, with data collected from various hospitals in the Kathmandu Valley. A structured questionnaire was employed to gather responses from patients, and statistical analysis was conducted using SPSS.The findings of this study contribute to the growing body of research on the role of healthcare providers' interpersonal attributes in improving patient satisfaction. By understanding the link between nurses’ personality traits and patient satisfaction, healthcare institutions can implement targeted interventions to enhance service quality and patient outcomes.